Law Enforcement Problems Against Cyber Crime Performed Through Phishing Method - Yusep Ardian; Ujuh Juhana; Haidan Angga Kusumah (Rechtsnormen: Journal of Law, 2023)
Background. Technology can be said to be a "double-edged sword" because it is developing very rapidly, many people use it to make life easier, but behind that the speed of technology is used as a tool to commit crimes and create new problems in the form of cyber crime, namely phishing. Purpose. The purpose of this research is to find out how law enforcement against cybercrime cases committed through the phishing method. The method used applies a qualitative method that focuses on looking at social phenomena that occur in society. Method. The method used applies a qualitative method that focuses on looking at social phenomena that occur in society. Results. The results showed that the Justice System has a major influence in the process of upholding law and justice starting from the Police level, the Prosecutor's Office to the Court Decision, besides that the ability of law enforcers to eradicate cybercrime is still limited in several ways such as, facilities and facilities, lack of expertise of law enforcement officials in handling cyber crackers, lack of police access to the latest information technology, and lack of public awareness and knowledge which will result in many obstacles. Conclusion. The point is that the legal framework in the field of technology must be able to keep up with the rapid advancement of technology, although there are already laws governing these crimes, they need to be updated to reflect the progress of increasingly modern times and the variety of cyber crimes that may occur in the future.